Dietary polyphenol canolol from rapeseed oil attenuates oxidative stress-induced cell damage through the modulation of the p38 signaling pathway. Issue 43 (5th July 2018) - Xia, Xiaoyang; Xiang, Xia; Huang, Fenghong; Zheng, Mingming; Cong, Renhuai; Han, Ling; Zhang, Zhen
Abstract : Canolol extracted from rapeseed oil attenuated oxidative stress-induced apoptosis and cellular redox status imbalance by inhibition of p38 phosphorylation. Abstract : Canolol (CAO) is a main phenolic compound with remarkable antioxidative properties that is generated in rapeseed oil during microwave pressing. The objective of this study was to identify the protective effect of CAO in hydrogen peroxide (H2 O2 )-triggered oxidative stress and reveal the role of the p38 MAPK pathway during the protective process. CAO treatment showed an observable cytoprotective effect. Results showed that CAO significantly improved H2 O2 -stimulated cell death, and diminished ROS production and malondialdehyde (MDA) level. Moreover, CAO increased glutathione (GSH) content and promoted the activities of superoxide dismutase (SOD) and catalase (CAT). As a result, apoptosis was ameliorated and depletion of the mitochondrial membrane potential was restored. Western blotting analysis demonstrated CAO downregulated the expression of caspase-3 and decreased the ratio of Bax/Bcl-2. Notably, the phosphorylation of p38 MAPK was inhibited by CAO in H2 O2 -induced apoptosis, which was confirmed by its inhibitor (SB203580). Taken together, our study demonstrated the pivotal role of the p38 MAPK pathway in the cytoprotective effect of CAO on oxidative stress-induced cell damage, suggesting CAO is a promising antioxidant in food and health-related fields.